2013
DOI: 10.1152/ajprenal.00387.2013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of growth differentiation factor 15 augments renal damage in both type 1 and type 2 models of diabetes

Abstract: Growth differentiation factor 15 (GDF15) is emerging as valuable biomarker in cardiovascular disease and diabetic kidney disease. Also, GDF15 represents an early response gene induced after tissue injury and studies performed in GDF15 knockout (KO) mice suggest that GDF15 plays a protective role after injury. In the current study, we investigated the role of GDF15 in the development of diabetic kidney damage in type 1 and type 2 models of diabetes. Renal damage was assessed in GDF15 KO mice and wild-type (WT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Abulizi et al [28] have determined that GDF-15 deficiency in a lipopolysaccharide-induced renal injury model aggravates renal damage. Other investigators demonstrated that genetic deletion of GDF-15 exacerbated injury in the renal interstitium and tubules in diabetic mice [29]. Based on these findings, we deduce that GDF-15 expression increases in the relatively early stage of renal injury to protect from tissue damage and is therefore able to predict disease by comparing this increase to the degree of tissue injury.…”
Section: Discussionsupporting
confidence: 61%
“…Abulizi et al [28] have determined that GDF-15 deficiency in a lipopolysaccharide-induced renal injury model aggravates renal damage. Other investigators demonstrated that genetic deletion of GDF-15 exacerbated injury in the renal interstitium and tubules in diabetic mice [29]. Based on these findings, we deduce that GDF-15 expression increases in the relatively early stage of renal injury to protect from tissue damage and is therefore able to predict disease by comparing this increase to the degree of tissue injury.…”
Section: Discussionsupporting
confidence: 61%
“…In this study of two independent, well characterized CKD cohorts, we found intrarenal GDF15 expression in the tubulointerstitial compartment of patients with CKD is reflected by circulating GDF-15 levels, which are significantly associated with disease progression, as defined by continuous decline of eGFR or reaching a composite end point of 30% decline in eGFR or progression to ESRD, independent of other risk factors for progression of kidney disease, including (15) 53 (14) 58 (15) 59 (16) 63 (13) 62 (12) 55 (11) 64 (12) 66 (12) 66 (12) Women, % 128 (15) 136 (22) 136 (20) 142 25133 20129 21134 20134 (19) 136 (20) eGFR 9 In a study of type 1 diabetic patients with nephropathy, elevated GDF-15 was associated with more rapid decline in eGFR but not progression to ESRD. 10 In two recent analyses of patients undergoing coronary artery bypass graft surgery, preoperative elevated GDF-15 was associated with postoperative AKI.…”
Section: Discussionmentioning
confidence: 73%
“…In mouse models of type 1 and type 2 diabetes, GDF-15 knock-out mice displayed increased tubular damage, with evidence of glucosuria and polyuria, as well as increased interstitial damage, as indicated by increased a-smooth muscle actin staining and collagen type 1 expression. Increased expression of GDF15 mRNA in outer medullary collecting duct cells has been reported during metabolic acidosis 14 and potassium depletion, 15 and both are associated with reduced kidney function. Data further suggest that GDF-15 not only can modulate the renal extracellular matrix production through an indirect route other than the Smad signaling pathway, but may also enhance cellular proliferation of tubular epithelial cells through noncanonic MAP kinase signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…b Values are reported per one increment for these biomarkers that were analyzed as ordinal variables and per SD for the other biomarkers that were analyzed as continuous variables. (11); evidence that murine deletion of the GDF15 gene increases atherosclerosis (12), renal damage (13), and body weight (14); and evidence that the expression of GDF15 suppresses inflammation (12,13).…”
Section: Discussionmentioning
confidence: 99%